THE EFFECT OF TYPE II DIABETES MELLITUS TO TUBERCULOSIS TREATMENT OUTCOME : A SYSTEMATIC REVIEW - Giovani, Calista; Monica Carissa, Theodora; Priska Adelin, Claudia (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: The converging epidemics of non-communicable disease like DM (DM) and an infectious disease like tuberculosis (TB) is a double burden. DM is increasing in the same population that is at high risk for developing TB. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 1199 articles, whereas the results of our search on SagePub brought up 892 articles. The results of the search conducted for the last year of 2013 yielded a total 30 articles for PubMed and 13 articles for SagePub. In the end, we compiled a total of  5 papers, 2 of which came from PubMed and 2 of which came from SagePub. We included five research that met the criteria. Conclusion: In summary, DM plays a salient role among TBDM patients. Our results showed that even a doubling risk for poor treatment outcome would have substantial population impact—up to 25 of deaths in TB patients could be attributable to DM. These findings are not only important for lowmiddle income countries that have high TB incidence and high DM prevalence, but also important for high income countries with sub-populations that have higher risks of both conditions. Screening programmes for DM among TB patients should be implemented in primary care especially in regions that have high-incidence of TB. Further studies are needed to explore the optimal treatment plan and glycaemic control among TB-DM.